The Prayuth Regime: Embedded Military and Hierarchical Capitalism in Thailand. Issue 2 (30th July 2018) - Kongkirati, Prajak; Kanchoochat, Veerayooth
Abstract: This paper explores the Prayuth regime, which began with a military coup in May 2014. Politically, we indicate how the junta has embedded its power in ways different from the past. It does not pursue a power-sharing governance as in the Prem and Surayud governments, but tries to militarise the cabinet, parliament, and even state-owned enterprises. The new constitution is designed to institutionalise the power of the military and the traditional elite vis-à-vis the electoral forces. Ironically, however, the junta's rule by military decree and discretionary power have weakened the bureaucratic polity, rather than strengthening it. Economically, the Prayuth regime forms a partnership with a group of Sino-Thai conglomerates to establish the Pracharath scheme, with an aim to differentiate its grass-roots development policy from Thaksin's populism (Prachaniyom). Nonetheless, it has become a platform through which the giant firms perform the leading role of 'Big Brother' in supervising small businesses in their sectors. Pracharath therefore reflects the collective endeavours of the conglomerates to replace competitive markets with hierarchy, rather than encouraging local firms to catch-up with them.